E-126 Endovascular treatment decision in acute stroke in patients with severe comorbidities – insights from an international multidisciplinary survey. (22nd July 2019) - Ospel, J; Kashani, N; Heo, J; Cherian, M; Kim, B; Rabinstein, A; Fischer, U; Baxter, B; Foss, M; Turjman, F; Sylaia, P; Yoshimura, S; et al.
Abstract : Background: Endovascular therapy is a highly effective treatment in previously-independent patients. In patients with severe comorbidities, the risks and benefits of endovascular treatment have to be balanced with the life expectancy and treatment risks. We explored the attitude of physicians towards endovascular treatment decision in patients with severe physical comorbidities. Methods: We conducted an international cross-sectional survey among 607 stroke physicians and interventionalists to understand their current practice and therapy decision-making in acute stroke. Participants were asked to give their treatment approach to 10 out of 22 randomly assigned case scenarios, 4 of them involving severe comorbidities (A: heart failure, COPD and renal insufficiency requiring dialysis, B: Stage IV metastatic prostate cancer, C: Non-metastatic prostate cancer with hormonal treatment, D: Rheumatoid arthritis requiring care in a nursing home). In all of those 4 scenarios, the patients had proximal ICA/MCA occlusions and were otherwise EVT-eligible. Results: In total, 6070 responses for 22 scenarios were obtained (276 responses for scenario A, 275 for scenarios B and D, 277 for scenario C). 92% of respondents decided in favor of EVT in scenario A, 72.7% in scenario B, 80.5% in scenario C and 90.2% in scenario D. Except of scenario B, those proportions were slightly higher than the average overall EVT decision rate (75.2%). Conclusion: If EVT criteria are otherwise fulfilled, moderate and even severe physical comorbidities were not considered as reasons to refrain from endovascular therapy in this survey. Disclosures: J. Ospel: None. N. Kashani: None. J. Heo: None. M. Cherian: None. B. Kim: None. A. Rabinstein: None. U. Fischer: None. B. Baxter: None. M. Foss: None. F. Turjman: None. P. Sylaia: None. S. Yoshimura: None. W. Kunz: None. B. Campbell: None. A. Wilson: None. M. Almekhlafi: None. G. Saposnik: None. M. Hill: None. M. Goyal: None. B. Menon: 1; C; unrestricted research grant by Stryker to the University of Calgary.